2020
DOI: 10.1007/s43032-020-00262-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Uterine Tissues During Peri-Implantation Period in Mice with Experimentally Induced Adenomyosis that Treated with anti-Ngf: Implications for Cell-Cell Adhesion and Metabolic Processes

Abstract: Nerve growth factor (NGF) has been verified to be expressed with higher level in adenomyosis uteri, and its neutralizing antibody has a strong inhibitory influence on inflammation. The present study aimed to explore the effect of anti-NGF on the expression of proteins in uteri of mice-induced adenomyosis and assessed its potential role in improving pregnancy rate. In this study, we established a mouse model of adenomyosis and administrated NGF-neutralizing antibody into mice. The mass spectrometry (MS) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…DhMGs may be related to adenomyosis and other gynecological diseases. At the same time, the protein interaction network (Figure 2C-D) showed that these genes including JAK2 that regulate macrophages, CDC42 that regulate cell morphological migration, MAPK1 that participate in immunomodulation, EGFR activation, and cell proliferation, HIF1A that participate in energy metabolism and activating gene transcription, and ITGB1 that participate in cell repair and metastasis [47][48][49][50][51][52] , are signi cantly related to the molecular mechanism and clinical symptoms of adenomyosis.…”
Section: Hmc Pro Les Differ Between Adenomyosis Patients and Healthy ...mentioning
confidence: 99%
“…DhMGs may be related to adenomyosis and other gynecological diseases. At the same time, the protein interaction network (Figure 2C-D) showed that these genes including JAK2 that regulate macrophages, CDC42 that regulate cell morphological migration, MAPK1 that participate in immunomodulation, EGFR activation, and cell proliferation, HIF1A that participate in energy metabolism and activating gene transcription, and ITGB1 that participate in cell repair and metastasis [47][48][49][50][51][52] , are signi cantly related to the molecular mechanism and clinical symptoms of adenomyosis.…”
Section: Hmc Pro Les Differ Between Adenomyosis Patients and Healthy ...mentioning
confidence: 99%
“…Additionally, the intrauterine microenvironment, provided mostly by glandular secretions, is crucial for implantation. Certain inflammatory conditions, such as adenomyosis or polycystic ovarian syndrome, induce an aberrant implantation process, reducing the pregnancy rate [6,7]. Pituitary suppression with a GnRH agonist before embryo transfer could suppress the hypothalamic-pituitary-gonadal axis and theoretically create better endometrial-embryonic synchronization and microenvironment for fertilization.…”
Section: Introductionmentioning
confidence: 99%